Influence of catalyst ink mixing procedures on catalyst layer properties and in-situ PEMFC performance - Jacobs, Clayton Jeffrey (Centre for Catalysis Research, 2017)
Despite the benefits of fuel cell technology its advancement to being commercially functional is hindered by a number of crucial factors. These factors are often associated with the lack of appropriate materials or manufacturing routes that would enable the cost of electricity per kWh to compete with existing technology. Whilst most research efforts have been directed towards developing more active catalysts, the amount of catalyst required in the fuel cell can be further reduced by improving the platinum utilisation in the membrane electrode assembly. The platinum utilisation is a strong function of the catalyst layer preparation step and there remains significant scope for optimisation of this step. Whereas significant work has been conducted into the different components of the catalyst ink there is limited work and understanding on the influence of the mixing method of the catalyst ink. This study will focus on the influence of the mixing technique on the catalyst ink properties and on the final fuel cell performance. Specifically, the study will investigate the effect of the three different mixing techniques on (i) catalyst ink quality (ii) the physical properties of the resultant catalyst layer and (iii) the in-situ electrochemical performance of the membrane electrode assembly. A large set of characterisation techniques were chosen to effectively study the step wise processing of the catalyst layer, and fuel cell performance. The results presented here include a comparison of the various mixing techniques and a comprehensive 2 x 2 factorial design into the individual techniques. The results suggest that high energy mixing is required for effective distribution of catalyst layer components, an even catalyst layer topography and a highly functional ionomer network which consequently, enhances performance. The mixing energy referred to involves prolonged mixing time, enhanced mixing intensity or a combination of the two. During bead milling of catalyst inks, high intensity mixing seems to be beneficial however, prolonged mixing time appears to be detrimental to the ionomer film structure. During high shear stirring and ultrasonic homogenisation of catalyst inks, the ink mixture significantly heats up. It has been observed that at higher temperatures, Nafion elongates and the contact with catalyst agglomerates is enhanced. High shear stirring of catalyst inks seems to be most effective at high agitation rates. High mixing energies result in high shear forces and in addition, high mixing temperatures which appear to be beneficial to establishing an effective catalyst/Nafion interface, enhancing the three phase boundary observed during in-situ testing. Ultrasonic homogenisation seems to be more effective at prolonged sonication times. Due to the erosive nature of ultrasonic dispersion, sufficient time is required to establish a well dispersed and distributed catalyst ink. However, the nature of particle size distribution resulting from ultrasonication shows that inks are unstable and is not recommended for high throughput processing. Overall, fuel cell performance is not significantly affected by the mixing step however; mixing does have an observable impact on catalyst layer formulation. Generally, when optimizing membrane electrode assembly fabrication, mixing parameters should be carefully chosen. This goes without saying that parameters need to be effectively studied before foregoing catalyst ink processing.